THE ANATOMY OF BONE HEALING: BONE REGENERATION IN ORTHOPEDIC MEDICINE - KHAN, QUA; MALIK, F; NAQVI, SAZ; KAUSAR, T; RAZA, T; MANSOOR, A (Biological and Clinical Sciences Research Journal, 2024)
Bone regeneration is a physiological bone formation process involved in routine fracture healing and continuous remodeling throughout adult life. The study’s main objective is to determine the role of orthopedic medicines in bone regeneration and healing process. This retrospective study was conducted in a public hospital in Karachi, Pakistan, from February 2023 to June 2023. The study aimed to collect data from 120 bone fracture patients and evaluate the progression of bone healing to identify critical determinants of successful regeneration. Clinical assessments, radiological imaging, and histopathological analyses were conducted to achieve the study’s objectives. The study collected data from 120 patients, with a mean age of 45.21±12.3 years. Of these, 70 were male and 50 were female. Upper extremities accounted for 40% of fractures, lower extremities 30%, and axial skeleton 30%. Simple fractures accounted for 50% of cases, while comminuted fractures represented 30% and open fractures 20%. There was a strong positive correlation between fracture severity and the time required for radiographic union, with a correlation coefficient (r) of 0.65 (p < 0.001). Additionally, biomarkers of bone turnover exhibited a moderate positive correlation with radiological healing, with a correlation coefficient (r) of 0.45 (p = 0.003). The study concludes that orthopedic interventions have a high success rate in achieving satisfactory outcomes, with the majority of patients experiencing successful bone healing and restoration of function.